Synthesis and characterization of nanostructured porous materials - Aljumialy, Abdulsalam Mohammed (2019)
Nanostructured porous materials have attracted significant research attention in recent years due to their interesting properties that may have relevance to many applications, including energy storage and environmental applications. There is a need for the development of porous materials synthesis methods offering simplicity, lower cost and more sustainable eco-friendly routes. The porous materials should have structural and textural characteristics similar or superior to those that are produced via conventional routes. The main objectives of this Thesis are to identify and investigate synthesis conditions for producing highly porous materials from low or zero value starting materials, such as waste biomass or hydrocarbon precursors. Chapter 1 gives a general background of nanostructured porous materials. It begins with a description of nanostructured materials and their classifications based of their structure, pore size and pore types. The nanostructured porous materials that are of interest for this thesis are also discussed and grouped based on their chemical compositions. The chapter covers the method of synthesising nanostructured porous materials and their important applications. Chapter 2 describes several techniques that have been used to investigate and characterize the synthesised porous materials. The use of porous materials in various applications is highly dependent on their properties. Gas adsorption methods are used for characterising the textural properties of porous materials, such as surface area, pore volume and pore size distribution. Chapter 3 presents an investigation on the effect of ion exchange in the use of zeolites for templating zeolite-templated carbons. Three ion-exchanged zeolites, (zeolite Y, 13X and ZSM-5) were used as hard templates, and acetonitrile and ethylene as carbon precursors via a one-step technique involving chemical vapor deposition (CVD) at temperatures between 600 and 800 oC. The zeolite templated carbons generated from the Ca-exchanged zeolites are found to exhibit high surface area (up to ca. 2300 m2/g) and pore volume (up to 1.26 cm3/g) depending on the template used and the carbon precursor (acetonitrile or ethylene). Chapter 4 presents an investigation of the synthesis of the mesoporous silicates, so-called mesocellular silica foams and their use as hard templates to generate mesoporous carbons with high pore volume and pore size. Acetonitrile was used as carbon precursor for the hard-templating process via a one-step technique involving chemical vapour deposition (CVD) at 900 °C under a nitrogen atmosphere. Chapter 5 explores the direct conversion of biomass to activated carbons in one step compared to multi-step conventional processes. It demonstrates the sustainable conversion of biomass, namely seaweed (Sargassum fusiforme) and palm-leaves, to activated carbons without the need for a carbonization step (hydrothermal carbonisation or pyrolysis). The effect of the direct route on the resulting porous carbons has been considered and compared to analogous carbons prepared via conventional methods. Furthermore, all the carbon samples were characterized to identify even subtle changes induced by the effect of varying synthesis parameters. The direct route offers advantages of low cost, simplicity, short operation time and enhanced porosity. Both conventional and direct activation used KOH as activation agent at KOH/biomass ratio of 2 or 4 and temperature of 600 to 800 °C. The directly activated carbons have large surface area of up to 3000 m2/g which is 30% higher than analogous conventionally activated carbon. Chapter 6 investigates the use of a less corrosive and less toxic activating agent i.e., potassium oxalate (PO) as a replacement of potassium hydroxide activation. The carbon precursor were added to the potassium oxalate at PO/carbon ratio of 2, 4, 5 or 6 and heated to a temperature of 600, 700, 800 or 900 °C in an inert atmosphere. The generated activated carbons have large surface area up to 2780 m²/g and pore volume of up to 1.3 cm³/g. The activated carbons are highly microporous with the proportion of micropore surface area being up to 91%. Varying the PO/carbon ratio does not have a significant effect on the porosity of the obtained carbons, wherein activation at PO/carbon ratio from 2 to 4, 5 or 6 leads to carbons with similar surface area. In contrast, the activation temperature had the critical role in controlling the textural properties at any given PO/ carbon ratio.